PEMANFAATAN LIMBAH CAIR INDUSTRI AREN DI DUKUH BENDO, DESA DALEMAN, KEC. TULUNG, KAB. KLATEN SEBAGAI PUPUK ORGANIK CAIR (POC) DENGAN METODE PENGOLAHAN AEROBIK - Jovita Irene Pongoh; Sarto -; Muhammad Sulaiman (ASEAN Journal of Systems Engineering, 2014)
These days, a lot of solid and liquid waste produced from aren powder indutry, and one of the area for this industry located in Bendo Subvillage, Klaten District, Central Java. The liquid waste is the unwanted product from of the aren powder during the screening and precipitation process.. The liquid waste produced by the industry at Dukuh Bendo is containing  high of BOD and COD and this is became an environmental disaster as most of the liquid waste did not through the waste treatment process, and sent directly to water stream so there is a need to overcome or minimize this whole problem, and the making of liquid organic fertilizer from the liquid waste of this industry is one of the solution. The usage of liquid organic fertilizer also can reduce the usage of chemical fertilizer and also can help repair the soil condition and minimize the environmental destruction caused by liquid waste from this industry.During the research, for the liquid waste treatment aerobic proces in the aeration pond is used with the addition of bacteria and varoius dilution composition; VAR1 the composition between liquid waste and water 50:50 with bacteria added, VAR2 the composition between liquid waste and water 80:20 with bacteria added, VAR3 the composition 100% liquid waste with bacteria added, VAR4 100% liquid waste with no bacteria added. From the laboratory test found that the liquid waste from aren industry contains 686 mg/l BOD and 5800 mg/l COD. The research was done in some stages; preliminary test to understand the characteristic of the liquid waste from aren powder industry, specially the BOD and COD levels,treatment in the aeration pond, and the result from the process ( liquid organic fertilizer) and it tested to cornstalk in this research and the height and the leaves growth are recordedThe result from aeration process with bacteria added are : the BOD with the efeective retention time for VAR2 is in day 4, with BOD level at 3.2 mg/l which is 98.8% reduced from the original level ( 686 mg/l). The COD with effective retention time for VAR2 is in day 4 with COD  level at 120 mg/l which is 96.98% reduced from the original level ( 5800 mg/l. The maximum nitrogen level is in day 5 at 0.07629%, phospor level at 0.0199% and potassium level at 0.0169%the positif growth of the cornstalk recorded during the period of the time showing that the nutrient absorbed properly.